Analisis Manajemen Perpustakaan dalam Menunjang Kegiatan Pembelajaran Di SMPN Karang Jaya Muratara - Murniyanto, Murniyanto (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This research was motivated by the suboptimal learning process at SMPN Karang Jaya, primarily caused by the limited availability of textbooks. Students have to take turns using books due to the small number of available copies. In addition, the school's library management is still not optimal, as indicated by the limited book collection and inadequate library facilities and infrastructure. The purpose of this study is to examine how library management supports the learning process. This research uses a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and documentation, with the main informants being the head librarian, the principal, and teachers. Data analysis techniques consist of data reduction, data presentation, and conclusion drawing. The findings of the study reveal that: (1) library planning is carried out through short-term, medium-term, and long-term programs; (2) library organization involves grouping collections and arranging the reading space functionally; and (3) the provision of learning resources such as books, reading areas, and book storage systems has been implemented, although still limited. Overall, library management at SMPN Karang Jaya is moving in a positive direction, but further improvements are needed to optimally support the learning process.